Poverty and the WTO - Hertel, Thomas W. (ed.) (New York, 2006)
Poverty reduction is deemed to be a centrepiece of the Doha Development Agenda (DDA) currently being negotiated under the auspices of the World Trade Organization (WTO). Yet there is considerable debate about the poverty impacts of such an agreement. Some are convinced it will increase poverty, while others are equally convinced that it will lead to poverty reduction. This book brings together the best scientific methods to bear on this question, taking into account the specific characteristics embodied in the DDA. Since the trade/poverty field is relatively new, a variety of different methods are utilized to be most appropriate for the varied countries featured. It consistently considers a range of complementary policies that might enhance the poverty outcome of the DDA, permitting poor households to take better advantage of new opportunities that might arise from such multilateral trade reforms. In addition, a fifteen- country study, coupled with the global analysis, allows the authors to draw more general conclusions about the poverty impacts of a prospective DDA.
Keywords: Poverty